Fanatisme Idol Korean Pop (K-Pop) terhadap Kesehatan Mental Remaja : Studi Komunitas BTS ARMY/@Army_Indonesia - Fathiyyah Mutmainnah; Sokhivah Sokhivah (Sosial Simbiosis : Jurnal Integrasi Ilmu Sosial dan Politik, 2025)
This research aims to determine the mental health condition of BTS fans in the BTS ARMY/ @Army_Indonesia community by looking at the influencing factors of fanaticism and the forms of activities carried out by BTS fans in the community. This research uses descriptive qualitative research methods. Data collection was carried out by means of interviews, observation and documentation and determining informants using purposive sampling. The research results show that Korean pop (K-pop) idol fanaticism on the mental health of teenagers in the BTS ARMY/ @Army_Indonesia community has an impact on their mental health so that it can be seen from the condition of emotional well-being which has a moderate level of fanaticism (personal intensity) such as BTS songs as inspiration, to convey emotions and feelings. Psychological well-being that has a high level of fanaticism (Borderline Pathological) such as, helping to heal oneself, calling BTS as a therapy tool, starting to be self-confident, to addiction, throwing away and not being able to share time with personal life. Social welfare that has a high level of fanaticism (Borderline Pathological), such as joining a community, adding to relationships, aggressive behavior, and breaking off friendships. The causes of adolescent Korean idol (K-Pop) fanaticism are influenced by several factors such as self-will, the environment, the desire to own objects, and the desire to interact with other people. Lack of awareness of oneself, parents and the environment is a challenge faced and can later increase fanaticism which has an impact on a person's mental health.